КОМПЕТЕНТНІСТЬ МАЙБУТНІХ МЕНЕДЖЕРІВ-ЕКОНОМІСТІВ ЯК УМОВА ЇХ ПОДАЛЬШОЇ УСПІШНОЇ ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2008)
Socio-economic changes undergoing at present time, predetermine new demands for both a system of management as a whole and personnel management. Modern management at oil levels has to guarantee economy of Ukraine structure reconstruction: to create a new effective model of activity; to use rationally all kinds of resources; to respond promptly to the problems that arise at different spheres of activity and find ways of their effective solving.